Legal Review Of The Implementation Of Termination Of Employment Relationship With The Reason Of The Pandemic Covid-19 - Ansow, Gevano; Yulianto, Yulianto; Nugraheni, Ninis (JURNAL LEGALITAS, 2022)
The research entitled Legal Study of the Implementation of Termination of Employment for the Reason of the Covid-19 Pandemic aims first to analyze how the norms and provisions of laws and regulations are applied related to the implementation of termination of employment in Indonesia and find out how legal protection is for workers who experience termination of employment. During the current Covid-19 pandemic. The research method used in this study uses a normative juridical research method with a statutory and conceptual approach. Based on the results of the research, it can be concluded First: the legal basis for employers in carrying out mass termination of employment relations with workers/laborers during the current Covid-19 pandemic for the first time referred to the provisions of Article 164 paragraph (1) of the Manpower Law which became the basis for the existence of emergency due to an unwanted cause then proceed with the implementation of Article 151 of the Manpower Law which regulates the process of terminating workers. Second, namely, the legal protection provided by the State for workers due to termination of employment due to the current Covid-19 pandemic first must provide workers' rights as in Article 156 of the Labor Law and, in the current period, must pay attention to the provisions in the Minister of Manpower Circular Letter Number M/3/HK.04/III/2020 concerning Worker/Labor Protection and Business Continuity in the Context of Prevention and Mitigation Covid-19 and Article 6 of the Quarantine Law and Health.